Determination of milk quality indicators and first streams depending on the stage of lactation and daily milk yield - Iryna Tkachova; Galina Prusova; Victoria Petrash; Anatoliy Tkachov; Vitaliy Petrash (Наукові горизонти, 2024)
The relevance of the study is to solve the problem of cow's milk quality and the influence of factors of lactation stage and daily milk yield on milk parameters, and to establish links between the content of somatic cells in milk and other milk parameters. The purpose of the study was to determine the influence of the lactation stage and daily milk yield on the quality indicators of milk and its first streams, and to establish links between the content of somatic cells and other indicators of the quality of milk and its first streams. Research methods – zootechnical (selection of groups, organisation of the experiment, determination of milk productivity, assessment of the stage of lactation, the level of milk yields, control milking), biochemical (determination of the main indicators of milk quality), statistical, mathematical. A significant difference between milk quality indicators in the daily milk yield and in the first three streams of milk (p≥0.95) was established, therefore, the need to separate the first streams of milk from the main milk yield was experimentally proved. It was found that the indicators of the quantity and quality of milk and its first streams in various degrees correlate with the stage of lactation, the highest daily milk yield was established in cows that were in the first trimester of lactation. Fluctuations in the quality indicators of milk and its first streams depending on the level of daily milk yield were established. It was found that the content of somatic cells in milk is quite significantly negatively associated with the indicators of lactose content and freezing point of milk, to a lesser extent – with daily milk yield, and positively – with the duration of lactation, protein and whey+casein content. In the first streams of milk, the correlation coefficients for milk productivity and quality did not exceed 0.250. The highest somatic cell content was positively correlated with the MSNF index, protein and whey+casein content, freezing point, urea content, and negatively correlated with daily milk yield and fat content. The findings can be used in milk production farms and when planning breeding work to improve the quality characteristics of milk by selection